Profil Kemandirian Belajar Matematika Santri Pondok Pesantren Selama Pandemi Covid 19 - Afinaningsih, Dissa; Jana, Padrul; Putri, Dhea Annisa; Aldianta, Linggar; Akhsani, Shofi Rizki; Siahaan, Kristianus Boby Anggiat Marito; Widayati, Widayati (Universitas Pekalongan, 2024)
The aim of this research was to analyze the mathematics learning independence of Islamic boarding school students during the Covid-19 pandemic. The sample in this study was 40 Al Imdad Bantul Islamic Boarding School students who were randomly selected. Data collection uses questionnaires and interviews. This type of research is qualitative research and is descriptive. The results of this research show that the level of independence in students' mathematics learning at the Al Imdad Islamic Boarding School during the Covid 19 pandemic has a level of independence in six indicators of students' learning independence, namely students have 82.5% self-confidence, 67.25% students are able to work alone, students are able to appreciate time 77.5%, students have a responsible nature 79.38%, students desire to compete to advance 74.22%, and students are able to make decisions 72.88%. Researchers concluded that students at the Al Imdad Islamic Boarding School did not have low levels of independence in learning mathematics.